Legal environment of the quality of gastronomic services (Review) (REDEL. Revista Granmense de Desarrollo Local, 2019)
The present article aims to address the legal environment that regulates the quality of gastronomic services internationally and in Cuba. To this end, a study was made of the theoretical-methodological aspects of the main foundations related to the quality of services. An analysis is made of the legal provisions most used at the international level and what are the regulations that govern the gastronomic services in Cuba for this type of service. A set of conclusions to be taken into account for future research.
Keywords: quality of services; legal environment; ISO International Standards